Mediation Effect of Customer Satisfaction on The Relationship Between Price Perception, Social Media, Brand Awareness, and Repurchase Decisions - Ritonga, Sri Endah; Digdowiseiso, Kumba (Graduate Program Magister Manajemen Pendidikan, 2023)
This study aims to determine the effect of perceived price, social media and brand awareness on repurchase decisions through customer satisfaction as a mediating variable for millennial consumers at KFC La Terrace Lenteng Agung. This research involved 200 samples of millennial consumers using a purposive sampling technique. Data collection was carried out by distributing questionnaires which were then analyzed by Stata 17.0 software using the SEM (Structural Equation Modeling) model. The results of this study indicate that price perceptions have a positive but not significant effect on customer satisfaction, while social media and brand awareness have a positive and significant effect on customer satisfaction. Meanwhile, social media, brand awareness, price perception, and customer satisfaction have a positive and significant impact on repurchasing decisions. In addition, price perception, social media, and brand awareness have a positive and significant influence on repurchase decisions mediated by customer satisfaction.